Analysis Of The Influence Of Work Discipline, Supervision And Workload On Employee Performance At The Badan Pengelolaan Keuangan Dan Aset Daerah Kota Medan - Eka Kurniati; Eli Delvi Yanti; Muhammad Yalzamul Insan (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the influence of work discipline, supervision, and workload on employee performance at the Medan City Regional Financial and Asset Management Agency. This study uses an associative quantitative approach with a sample of 42 employees selected through a saturated sampling technique. Data collection was carried out using a questionnaire, while data analysis used SPSS version 25 through validity, reliability, classical assumptions, multiple linear regression, t-test, F-test, and coefficient of determination tests. The results showed that work discipline had a significant effect on employee performance with a t-value of 2.840 > t-table 1.682 and sig. 0.000 < 0.05. Supervision also had a significant effect and became the dominant variable with a t-value of 6.438 > 1.682 and sig. 0.000 < 0.05. Workload had a significant effect with a t-value of 3.648 > 1.682 and sig. 0.000 < 0.05. Simultaneously, these three variables significantly influenced employee performance, with an F-value of 353.133 > F-table 3.03 and a significance level of 0.000 < 0.05. The Adjusted R² value of 0.949 indicates that 94.9% of the variation in employee performance is explained by work discipline, supervision, and workload, while 5.1% is influenced by factors outside this study.